Influence of body position on diaphragmatic thickening fraction in healthy adults: advancing the standardization of diaphragm ultrasonography - Arzayus-Patiño, Leonardo; Daza-Arana, Jorge Enrique; Anacona, Laura Rojas; Portilla, Isabella Villota; Vargas Campo, Laura Valentina; Wilches-Luna, Esther Cecilia (Frontiers in Physiology, 2026)
IntroductionThe diaphragm is the main respiratory muscle, and its dysfunction—particularly in hospitalized patients or those in intensive care units—is associated with difficulties in weaning from mechanical ventilation, functional deterioration, and increased healthcare costs. Although measurements such as maximal inspiratory and expiratory pressures (MIP and MEP), handgrip strength, and the Medical Research Council (MRC) scale allow for the estimation of global muscle strength, they do not directly assess diaphragmatic function. Ultrasonography has emerged as a precise and non-invasive technique for evaluating the diaphragm through parameters such as excursion, thickness, and diaphragmatic thickening fraction (DTF). However, body position during assessment introduces variability and limits protocol standardization, highlighting the need to clarify its influence in healthy individuals.ObjectiveTo determine the influence of changes in body position on diaphragmatic thickening fraction and diaphragm thickness assessed by ultrasonography in healthy adults from the city of Cali.MethodsA cross-sectional descriptive study was conducted in 36 healthy adults (18 men and 18 women) aged 18–65 years. A high-frequency linear probe (7–18 MHz) was used to assess the right hemidiaphragm in five body positions: supine (0°) and head-of-bed elevations of 30°, 45°, 70°, and 90°. Diaphragmatic thickening fraction, thickness at end-expiration, and thickness at end-inspiration were measured. Differences between positions were analyzed using Friedman’s test with post hoc comparisons, and additional analyses explored associations with age and body mass index.ResultsDiaphragmatic thickening fraction increased progressively with trunk inclination, reaching its highest value at 70°, followed by a significant decrease at 90° (p < 0.001). Significant differences across positions were also observed for diaphragm thickness at both end-expiration and end-inspiration (p < 0.001). Associations with age and body mass index were identified only at 90°, whereas intermediate positions showed a more stable diaphragmatic behavior. In sex-stratified analyses, significant differences were observed exclusively at 70°.ConclusionBody position significantly influences diaphragmatic thickening fraction, with 70° producing the highest values in healthy adults. These findings highlight the need to standardize posture during diaphragm ultrasonographic assessment to optimize diagnostic precision.